Memorandum of Understanding between the BRAC Development Institute, BRAC University and Institute of Development Studies (IDS), University of Sussex in connection with the project "Citizenship DRC" (2009) - lnstitute of Development Studies, University of Sussex; BRAC Development Institute, BRAC University (BRAC Development Institute (BDI) and Institute Development Studies, 2013)
1. Introduction. 2. Duration. 3. Terms of reference. 4. Budget. 5. Payment. 6. Legal status. 7. Other contractual conditions. 8. Correspondence. 9. Acceptance.